Comparing the support of the EU and the US for international human rights law qua international human rights law: Worlds too far apart? - Cali, Basak (Icon-International Journal of Constitutional Law, 2015)
Support for international human rights law (IHRL) is one area where most international lawyers would have a hunch that the European Union fares better than the United States overall. In this article I focus on Pollack's dependent variable, "support" for international law, and its four dimensions: leadership, commitment, compliance, and internalization and investigate this hunch. I find that the conventional contrast between the US and the EU with regard to their support for IHRL is valid, with respect to political support for IHRL, but less so for judicial support. I argue that the marked differences between the EU and the US in the field of political support for IHRL are best explained by the thickness of the institutional human rights regime with respect to EU member states In the case of judicial support, the CJEU shares with the US Supreme Court the reflex of protecting its own constitutional autonomy, despite the comparatively better legal resources at its disposal to support IHRL.
CRIS-Team Scopus Importer:2023-03-21